Hands-on chatbots with Google Dialogflow (Packt Publishing, 2018)
"Chatbots are voice-aware bots, i.e. computer programs designed to simulate human conversations with users. This course introduces Dialogflow, Google's conversational interface for bots, devices, and applications."--Resource description page